Centralization and Provincial Government in the Ottoman Empire A New Administrative Model the Province of Kurdistan (1847-1867) - ÜLKE, CEMAL (ROSSIISKAYA ISTORIYA, 2026)
This study examines the establishment and evolution of the Kurdistan Province, which was established in 1847 and was part of the Ottoman Empire’s eastern provincial organization. Formed within the context of Ottoman centralization policies, the Kurdistan Province presented a unique administrative model that differed from the classical Ottoman provincial system as it included local Kurdish beys in the administration, albeit for a short period. This period represents a multi-layered restructuring process in which the empire redefined the relationship between the center and the provinces, questioned classical administrative practices, and sought to increase the state’s influence over the community. The Tanzimat Edict and its reforms formed the normative framework of this restructuring; however, the real effects of the reforms were felt more in the provinces . Particularly towards the middle of the 19th century, following the Bedirhan Bey uprising, the Diyarbekir Province was merged with the Van, Muş, and Hakkâri districts, as well as the Cizre-Bohtan and Mardin districts. The article discusses the province’s administrative and legal status, the yurtluk-ocaklık system, the dynamics between central authority and local powers, and the dismantling of this structure during the Tanzimat Edict’s centralization process in the 19th century. DOI: 10.5281/zenodo.19615946